Human endogenous retroviruses and the inflammatory response: A vicious circle associated with health and illness - Rangel, Sara Coelho; da Silva, Michelly Damasceno; da Silva, Amanda Lopes; dos Santos, Juliana de Melo Batista; Neves, Lucas Melo; Pedrosa, Ana; Rodrigues, Fernanda Monteiro; Trettel, Caio dos Santos; Furtado, Guilherme Eustáquio; de Barros, Marcelo Paes; Bachi, André Luis Lacerda; Romano, Camila Malta; et al. (Frontiers in Immunology, 2022)
Human Endogenous Retroviruses (HERVs) are derived from ancient exogenous retroviral infections that have infected our ancestors’ germline cells, underwent endogenization process, and were passed throughout the generations by retrotransposition and hereditary transmission. HERVs comprise 8% of the human genome and are critical for several physiological activities. Yet, HERVs reactivation is involved in pathological process as cancer and autoimmune diseases. In this review, we summarize the multiple aspects of HERVs’ role within the human genome, as well as virological and molecular aspects, and their fusogenic property. We also discuss possibilities of how the HERVs are possibly transactivated and participate in modulating the inflammatory response in health conditions. An update on their role in several autoimmune, inflammatory, and aging-related diseases is also presented.